Hubungan Terpaan Peringatan Bahaya Merokok Pada Kemasan dan Tingkat Kepercayaan Akan Bahaya Merokok dengan Minat Mengurangi Merokok - Pradipta Winanda; Sri Widowati Herieningsih (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
This study is based on the high number of active smokers in Indonesia. The government has made various efforts to reduce the rate of tobacco consumption in Indonesia. One of the government's done is by issuing a warning of the danger of smoking on cigarette packaging. This study aims to know to know the exposure relationship of warning about the danger of smoking on cigarette packaging and the level of confidence about the dangers of smoking with the interest of reducing smoking with the number of samples of 60 respondents with the provisions of the students who become active smokers. The results from the research revealed that there are corelations between exposure variable warning of smoking with variable interest in reducing smoking by using the theory of Cognitive Response Model can be proven through Kendall's Tau correlation analysis yields a significance number of 0,000 or stated very significant and correlation coefficient value of 0.586. This result show that strong conection.Meanwhile, in the second result it is known that there is a relationship between the variables of the level of confidence in the dangers of smoking with an interest in reducing smoking. The second hypothesis uses the theory of Motivational Protection, with Kendall's Tau correlation analysis yielding a significance number of 0,03 or very significant and correlation coefficient of 0.323. This result show that strong conection.